Dampak Edukasi Berbasis Video terhadap Pengetahuan Remaja tentang Bantuan Hidup Dasar - Sitti Rahmatia; Nur Alya Aprilianti; Muhammad Basri (Celebes Advance Health Journal, 2025)
Background: Adolescents' knowledge of Basic Life Support (BLS) is still limited, even though this age group has the potential to be the first witnesses to cardiac arrest. Engaging educational media is needed to improve their understanding of the procedural steps of BLS. Objective: This study aimed to assess the effectiveness of educational videos in improving adolescents' knowledge of BLS at SMAN 1 Gowa. Methods: The study design used a pre-experimental approach with a one-group pretest–posttest model involving 30 students selected through a purposive sampling technique. Knowledge was measured before and after the intervention using a digital questionnaire, while satisfaction with the video media was assessed through a survey form. Results: The results showed a significant increase in knowledge, marked by a change in the good knowledge category from 63.3% in the pre-test to 100% in the post-test. All respondents also considered the video media to be interesting and easy to understand. These findings indicate that educational videos are effective in conveying basic BLS skills and can improve adolescents' knowledge retention. Conclusions: Video media can be an appropriate and efficient learning strategy to improve adolescents' preparedness in facing emergencies and has the potential to be integrated into school health education programs.